CSR committee and corporate social performance: Do capitalism models matter? - Elage, Adam; Ben Larbi, Sami; Meniaoui, Jihène; Dardour, Ali (Management international / International Management / Gestiòn Internacional, 2026)
Our study examines the impact of CSR committees on corporate social performance (CSP) and the moderating effect of capitalism models on this relationship.Using an international sample of 2,066 firm-year observations from 2011 to 2018 across 13 countries, the study employs a multi-theoretical approach combining neo-institutional theory, stakeholder theory, and resource dependence theory. CSP is measured using two approaches: process-based (Wood, 1991) and stakeholder-based (Clarkson, 1995).Our results show that CSR committees significantly improve CSP, with a more pronounced effect in coordinated market economies (CMEs) than in liberal market economies (LMEs). This study highlights the importance of institutional factors in the effectiveness of voluntary governance mechanisms and offers implications for regulators and actors in various national contexts.